2000
DOI: 10.1097/00007890-200002150-00009
|View full text |Cite
|
Sign up to set email alerts
|

Disaccharidase Activities and Fat Assimilation in Pediatric Patients After Intestinal Transplantation

Abstract: The results of this investigation show that, in the absence of histologic or clinical indications of allograft rejection, pediatric intestinal transplant recipients do not have primary disaccharidase deficiencies. Similarly, absorption of usual dietary lipid content is adequate once weaning from parenteral nutrition is complete. In contrast, early assimilation of vitamin E is poor. Vitamin E absorption subsequently improves, but the mechanism is obscure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 20 publications
4
22
0
Order By: Relevance
“…Moreover, our results are in accordance with the findings of Cahn et al (2005). The exact mechanism responsible for simultaneous and similar histopathological changes in the skin and in the solid transplanted organ is not clear; however, there are several possible reasons such as ischaemia-reperfusion injury, intestinal lymphatic disruption and lymphatic tissue activation, immunosuppressive drug activity and toxicity, and the role of chronic antigen-antibody activity and stimulation (Kaufman et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, our results are in accordance with the findings of Cahn et al (2005). The exact mechanism responsible for simultaneous and similar histopathological changes in the skin and in the solid transplanted organ is not clear; however, there are several possible reasons such as ischaemia-reperfusion injury, intestinal lymphatic disruption and lymphatic tissue activation, immunosuppressive drug activity and toxicity, and the role of chronic antigen-antibody activity and stimulation (Kaufman et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The clinical symptoms of intestinal ACR are fever, nausea, vomiting, abdominal distension, abdominal pain, skin rashes, and they can progress to septic shock (Kaufman et al, 2000;Cicalese et al, 2000;Gulbahce et al, 2003). The final diagnosis of ACR is confirmed by histological analysis of endoscopically guided mucosal biopsies.…”
mentioning
confidence: 99%
“…In a recent report from the French team regarding the long-term nutritional outcome of transplanted children, the most striking finding was severe steatorrhea, resulting in an energy absorption 5-10% lower than normal [17 ]. Another study also reported a mean coefficient of lipid absorption of only 86% in a group of 22 children at different posttransplant times [15]. The main hypothesis is that fat malabsorption is due to an insufficient reestablishment of a functional lymphatic circulation.…”
Section: Long-term Intestinal Function and Growthmentioning
confidence: 96%
“…Oral intake can be introduced while still advancing tube feeds, particularly in those without oral aversion. Early posttransplantation, the osmolality of feeds affect stomal output and, therefore, it is prudent to limit high sugar containing foods [15]. Some programs, like the French one, also avoid dairy products early after transplant because there is thought to be lactose malabsorption responsible for an increase in stool output and also an increased incidence of allergies to food proteins posttransplantation possibly related to altered mucosal permeability and T-cell responses due to immunosuppressive drugs [16].…”
Section: Type and Mode Of Enteral Feeding Deliverymentioning
confidence: 99%
“…Mortality is not of course the only issue. The recent emphasis on quality of life [14] and long-term graft function [15] is most appropriate, as the final judgment on the relative risks and benefits of HPN versus transplantation must take all of these factors into account.…”
Section: Indications and Patient Selectionmentioning
confidence: 99%